2011
DOI: 10.1016/j.dental.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMPs by alcohols

Abstract: Objectives While screening the activity of potential inhibitors of matrix metalloproteinases (MMPs), due to the limited water solubility of some of the compounds, they had to be solubilized in ethanol. When ethanol solvent controls were run, they were found to partially inhibit MMPs. Thus, the purpose of this study was to compare the MMP-inhibitory activity of a series of alcohols. Methods The possible inhibitory activity of a series of alcohols was measured against soluble rhMMP-9 and insoluble matrix-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
0
47
0
5
Order By: Relevance
“…1,5,6 Infiltration of hydrophobic monomers decreases water sorption and solubility and resin plasticization and may prevent or at least reduce enzymatic hydrolysis of collagen. [144][145][146][147] Together, these would lead to improved bond durability. 1,6 Currently, however, technique sensitivity and generally long treatment times prohibit ethanol-wet bonding in clinical settings, and more user-friendly and reproducible techniques or materials need to be developed for everyday use.…”
Section: Ethanol-wet Bondingmentioning
confidence: 99%
“…1,5,6 Infiltration of hydrophobic monomers decreases water sorption and solubility and resin plasticization and may prevent or at least reduce enzymatic hydrolysis of collagen. [144][145][146][147] Together, these would lead to improved bond durability. 1,6 Currently, however, technique sensitivity and generally long treatment times prohibit ethanol-wet bonding in clinical settings, and more user-friendly and reproducible techniques or materials need to be developed for everyday use.…”
Section: Ethanol-wet Bondingmentioning
confidence: 99%
“…The measurement of the loss of dry mass after 30-day incubation was used as an indirect measure of the proteases activity [25][26][27]. The dry mass of each beam was measured at the beginning and at the end of the 30-day incubation period.…”
Section: Loss Of Dry Mass Over Timementioning
confidence: 99%
“…Tezvergil-Mutluay et al [25] have shown that both soluble and dentine-matrix bound MMPs could be inhibited by alcohols; hence, the solvents used in the delivery of CHX during the dentine bonding procedure may be more crucial than that was thought. The solubility of CHX may also be different in different solvents.…”
Section: Introductionmentioning
confidence: 97%
“…The inhibitor may act as an allosteric one and interacts with the protein at a region different from the active site of the enzyme, or it may interact directly with the active site. Aliphatic alcohols are competitive inhibitors of metalloenzymes since they coordinate the metal ion in the enzyme's active site [Tezvergil-Multuay et al, 2011;Wójcik et al, 2011]. None of the studied aliphatic alcohols inhibited enzyme activity at any of the tested concentrations ( table 3 ).…”
Section: Enzyme Activity In the Presence Of Inhibitorsmentioning
confidence: 99%
“…Bertini et al [1994] observed a similar effect for catechol 2,3-dioxygenase. Methanol, as a lowmolecular alcohol, did not activate the examined enzyme due to its strong hydrogen interaction with the enzyme [Tezvergil-Multuay et al, 2011]. The enzyme with iron ion located in the active site of the enzyme can be inhibited by chelators [Gopalan et al, 1989].…”
Section: Enzyme Activity In the Presence Of Inhibitorsmentioning
confidence: 99%